IMPLEMENTASI LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING PADA MATA PELAJARAN BIOLOGI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS KELAS X IPA 1 SMA NEGERI 1 SABAK AUH - Irma Oktamadila Tsaniyah; Sri Wulandari; Firdaus LN Firdaus LN (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to improve the critical thinking skills of students in class X IPA.1 SMA Negeri 1 Sabak Auh through the implementation of student worksheets based on problem based learning. This research method is Classroom Action Research which is carried out in 2 cycles. Each cycle consists of the planning stage, the implementation stage, the observation stage and the reflection stage. The research was carried out at SMA Negeri 1 Sabak Auh in September - November 2018. The parameter measured was critical thinking ability seen from students' answers on the worksheet and assessed using a critical thinking ability assessment sheet. The data obtained were analyzed descriptively. The results of this study showed the average value of critical thinking skills in the first cycle was 74.19 (enough category) and increased in the second cycle to 84.39 (good category). Based on these data, it can be concluded that the application of student worksheets based on problem based learning can improve the critical thinking skills of students in class X science. 1 SMA Negeri 1 Sabak Auh.Key Words : Creative Thinking Skills, Discovery Learning, Worksheets